Dampak Sampah Plastik Bagi Ekosistem Perairan - Ahmad Fahrizal; Muhaiminah Akib (LP3M Universitas Muhammadiyah Sorong, 2020)
The purpose of the service to high school/vocational high school, and junior high school students in malagusa Village, Aimas Distric, Sorong Regency is to provide knowledge and understanding to students about waste and plastic waste, types of plastic waste, the solution ecosystem. The method used is a lecture and demonstration method with sxhool students in Kelurahan Malagusa about waste and its handling. The results of the implementation of this community service where students attending Malagusa Village were(1) appreciation of the local government in this case the Malagusa village Government in this case the Malagusa Government regarding the seminar activities carried out (2) the high motivation of the community service seminar participant coming from Vocational, high school and junior high school students the whole village of Malagusa with liveliness asking questions at the discussion session guided by the activity organizing committee. (3) Increaasing students’ understanding, knowledge and ability in understanding about waste and increasing waste for the environment.